1993
DOI: 10.7863/jum.1993.12.6.323
|View full text |Cite
|
Sign up to set email alerts
|

Caudal regression versus sirenomelia: sonographic clues

Abstract: Seven cases with the pathologic/autopsy diagnosis of caudal regression or sirenomelia in which antenatal sonography had been performed were reviewed. The three patients with caudal regression had similar findings on antenatal sonogram, including normal or increased amniotic fluid, mild dilation or normal urinary systems, nonfused extremities, and sacral agenesis. In the four patients with sirenomelia, common sonographic findings included marked oligohydramnios, suspected renal agenesis, and sacral agenesis. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 3 publications
(3 reference statements)
1
74
0
5
Order By: Relevance
“…Twickler et al 3 reported the differences between these two conditions after examining four cases of sirenomelia and three cases of CRS (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twickler et al 3 reported the differences between these two conditions after examining four cases of sirenomelia and three cases of CRS (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…10 However, history of maternal diabetes is present in only 16% to 22% of infants with CRS. 3 Unlike CRS, sirenomelia is rarely associated with maternal diabetes 11 and more frequently with increased incidence of monozygotic twinning. 12 Sirenomelia is thought to be due to an abnormal vascular pattern 13 because these patients usually have a single umbilical artery arising from high in the abdominal cavity, and this may, therefore, divert blood flow away from the caudal region, leading to its underdevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Bu durumun erken dönemde fark edilmesi ve ikinci trimesterdeki sonografik değerlen-dirmede her iki alt ekstremitenin birlikte tek femur gibi hareket etmesi hastalığın tanınmasında önemlidir. [3] Tıbbi yazılarda sirenomelili olgular polidaktili, vertebra anomalileri, anal atrezi, renal agenezi, mesane agenezisi ve kosta sayısının eksik olması gibi birçok anomali ile birlikteliği rapor edilmiştir. [4] Sunulan olgu literatür-de bildiğimiz kadarıyla sirenomeli ile 13 kosta ve 13 adet torakal vertebra sayısı birlikteliği olan ilk olgudur.…”
Section: Introductionunclassified
“…La proximidad y yuxtaposición entre el intestino posterior en desarrollo, el aparato genitourinario, la notocorda, y estructuras neurales, explica la asociación conjunta de malformaciones de los sistemas neurológico, vertebral, anorectal, renal y genital, comúnmente observadas en el SRC 8,13 . Por otro lado, se cree que la sirinomelia y sus defectos asociados serían atribuibles a un robo de fl ujo que condicionaría una isquemia severa hacia el hemicuerpo distal 3,[14][15][16] . En estos pacientes se ha observado un vaso aberrante derivado de la arteria vitelina que redirige sangre desde la aorta abdominal hacia la placenta por medio del cordón umbilical.…”
Section: Introductionunclassified
“…Por este motivo, es que a pesar que la sirinomelia es usualmente considerada como la forma más severa de SRC, algunos autores sugieren que ambas condiciones conformarían entidades separadas debido a su patogenia distinta. En este sentido, Twickler et al, en el año 1993 des cribió por primera vez las diferencias entre estas dos condiciones después de examinar 4 casos de sirinomelia y 3 casos de SRC 15 . Dentro de las características descritas que defi nen la sirinomelia y la distinguen de un SRC se encuentran: la presencia de una arteria umbilical única, agenesia caudal más severa (extremidad inferior única o dos fusionadas), alteraciones renales severas e incluso letales (agenesia renal o displasia severa), ausencia de malformaciones anales y oligohidroamnios 15 .…”
Section: Introductionunclassified